The shape of the human adult trachea among Bangladeshi males (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: trachea; cross-sectional shape; endotracheal; CT scandoi: 10.3329/jcmcta.v18i2.3832Journal of Chittagong Medical College Teachers' Association 2007: 18(2):26-27